PERBANDINGAN SOFTWARE DRIVE TEST DALAM UJI KUALITAS JARINGAN 3G MENGGUNAKAN PROVIDER TELKOMSEL - Hana Graceila Sitindjak; Ridwan Satrio Hadikusuma; Yuliarman Saragih (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2021)
Increasing the number of telecommunications infrastructure in Indonesia in accordance with customer needs for stability and speed of network access. Network measurement is required using the drive test method to ensure network quality within the service area. To do a drive test, you need software such as Net Monitor Lite, Nemo Handy, G-Net Track Lite and many more. Performance comparisons are needed to determine the quality of the software used when making measurements. So the measurements obtained using Net Monitor Lite, Nemo Handy and G-Net Track Lite for parameters RSCP, RSSI, RSRP, RSRQ and SNR need to be compared with performance. The comparison results show that the RSCP value between the theoretical measurements shows that the Net Monitor Lite measurement results are closer than Nemo Handy and G-Net Track Lite. For example, the difference between RSCP on eNodeB for Net Monitor Lite is 3.50 dBm, while for Nemo Handy, the difference is 4.15 dBm and 5.56 dBm for G-Net Track Lite software. This is due to the limited features in the G-Net Track Lite software which does not have a PCI lock feature so that at some measurement points it cannot be compared.